2016
DOI: 10.1002/2016gl068145
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ionospheric plasma bubble generation in more active ITCZ

Abstract: A close link between the atmospheric Intertropical Convergence Zone (ITCZ) and ionospheric plasma bubble has been proposed since the last century. But this relationship has often appeared to be less than convincing due to the simultaneous roles played by several other factors in shaping the global distribution of ionospheric bubbles. From simultaneous collaborative radar multibeam steering measurements at Kototabang (0.2°S, 100.3°E) and Sanya (18.4°N, 109.6°E), conducted during September–October of 2012 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 26 publications
2
50
0
Order By: Relevance
“…Atmospheric gravity waves from the troposphere are also suspected to influence the F-region vertical plasma drift (Li et al 2016) and play a role in the seeding and development of EPBs (e.g., McClure et al 1998;Tsunoda 2010a, b); atmospheric gravity waves therefore represent another form of forcing from below. One would expect that atmospheric gravity waves that seed EPBs would originate from a local source, whereas tides or planetary waves would be expected to exhibit larger scale, perhaps even global, effects.…”
Section: Discussionmentioning
confidence: 99%
“…Atmospheric gravity waves from the troposphere are also suspected to influence the F-region vertical plasma drift (Li et al 2016) and play a role in the seeding and development of EPBs (e.g., McClure et al 1998;Tsunoda 2010a, b); atmospheric gravity waves therefore represent another form of forcing from below. One would expect that atmospheric gravity waves that seed EPBs would originate from a local source, whereas tides or planetary waves would be expected to exhibit larger scale, perhaps even global, effects.…”
Section: Discussionmentioning
confidence: 99%
“…Su et al () studied the correlation between distributions between deep convective clouds in the ITCZ and plasma irregularities, and results indicated that correlations only exist in South American and African sectors. Li et al () suggested that enhanced plasma irregularity generation is caused by gravity waves in the more active ITCZ. Dramatic effects may occur in the ITCZ; Parrot et al () presented that maximal occurrence of spectacular emission events observed by the DEMETER occurred over the Atlantic which also lies in the ITCZ.…”
Section: Discussionmentioning
confidence: 99%
“…Various investigations have revealed the presence of large-scale longitudinal modulation of the ESF [eg., Kelley et al, 1981;Tsunoda, 1983]. It has been found that the equatorial plasma bubble does not occur continuously but has a longitudinal modulation much greater than the longitudinal dimension of an individual bubble [Tsunoda et al, 2011;Tulasi Ram et al, 2012;Li et al, 2013;Tulasi Ram et al, 2014;Tsunoda, 2015;Li et al, 2016]. This longitudinal modulation has been found to be related with the large-scale wave structure (LSWS) found in the evening F layer.…”
Section: Introductionmentioning
confidence: 99%